2005
DOI: 10.1213/01.ane.0000159868.06847.47
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Ropivacaine Anesthesia Decreases the Bispectral Index During the Awake Phase and Sevoflurane General Anesthesia

Abstract: The sedative effects of epidural anesthesia without volatile and IV anesthetics and quantification of the degree of epidural anesthesia-induced sedation have not been investigated. In the current study we evaluated the effects of epidural anesthesia on the bispectral index (BIS) during the awake phase and during general anesthesia. After placing the epidural catheter, the patients were randomly allocated to 2 groups receiving either 5 mL of epidural saline (group S) or the same volume of 0.75% ropivacaine (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 15 publications
2
22
1
1
Order By: Relevance
“…But in our study 8 of the 63 MDZ patients experienced respiratory depression requiring intervention. This might be due to the more fentanyl consumption or sedative function of epidural anesthesia which had been documented by some investigators [26,27]. Dexmedetomidine cannot cause respiratory depression [28,29]; this was confirmed in our study.…”
Section: Discussionsupporting
confidence: 85%
“…But in our study 8 of the 63 MDZ patients experienced respiratory depression requiring intervention. This might be due to the more fentanyl consumption or sedative function of epidural anesthesia which had been documented by some investigators [26,27]. Dexmedetomidine cannot cause respiratory depression [28,29]; this was confirmed in our study.…”
Section: Discussionsupporting
confidence: 85%
“…(Agarwal et al, 2004;Kanata et al, 2006) anesthetics in upper or lower abdominal surgery. Ishiyama et al(2005) recently reported that epidural ropivacaine anesthesia decreased the bispectral index (BIS) during the awake phase and during general anesthesia. A new report by Gaughen and Durieux (2006) demonstrated that inadvertent overdose of i.v.…”
Section: Introductionmentioning
confidence: 99%
“…We compared these two solutions because they are often used for upper abdomen epidural anesthesia during surgery in our institution and have approximately a 0.3 ratio, according to the results reported by Liu (1998) and Arakawa et al(2003), these two anesthesia solutions should provide the same analgesic effect. As in previous studies (Ishiyama et al, 2005;Kearse et al, 1998), we used the BIS as a sensitive measure of drug hypnotic effect. The BIS has recently been introduced as an estimation of anesthetic effect.…”
Section: Introductionmentioning
confidence: 99%
“…According to Sentürk et al [16], the BIS is not reduced by epidural anesthesia. However, according to Ishiyama et al [17], the BIS decreased when the patient was awake and under epidural anesthesia; yet, the reduction was with respect to the BIS levels in the awake state, and the BIS did not drop to levels as low as those during sedation (≤ 80). Therefore, the effect of epidural anesthesia itself on the BIS can largely be ignored.…”
Section: Discussionmentioning
confidence: 98%